Sunset Policy dan Implikasinya terhadap Peningkatan Penerimaan Pajak Penghasilan di Daerah Istimewa Yogyakarta - Dahliana Hasan (Fakultas Hukum Universitas Gadjah Mada, 2009)
Sunset policy is a policy which decreases the amount of administrative sanction in the form of interest. This policy is governed by Article 37A Act Number 28 of 2007. The target of sunset policy is the taxpayer who has good faith either to admit having insufficient payment of income tax or to have willed to register a tax file number (NPWP). However, the time of sunset policy is limited; it takes only 1 (one) year to apply the policy from 1 January to 31 December 2008. The research found that first, in tax law side sunset policy has the same legal meaning as kwijtschelding. The same legal meaning refers to the same characteristics found both in sunset policy and in kwijtschelding. Second, the internal target was not achieved until November 2008 as a result there was less contribution to the increasing amount of income tax revenue in DIY.